2021
DOI: 10.5093/apj2021a13
|View full text |Cite
|
Sign up to set email alerts
|

Public Attitudes towards Intimate Partner Violence against Women and Influential Factors in China and Spain

Abstract: According to United Nations (2012), between 15% and 76% women have been targeted for physical and/or sexual violence in their lifetime worldwide, which makes violence against women become a serious social problem. The most common type of violence against women is violence perpetrated by a current or former intimate partner, including physical, verbal, economic, or sexual violence, which 30% of women have experienced when being in a relationship (World Health Organization, 2013). For the purpose of this article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…In the same line, Gracia and Herrero (2005) and Yang et al (2021) reported that women accepted DVAW less than men. Regarding educational level and contrary to current results, educational level was significantly negatively associated with acceptability and justification of DVAW (Gracia et al, 2020; Gracia & Tomás, 2014; Tran et al, 2016).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In the same line, Gracia and Herrero (2005) and Yang et al (2021) reported that women accepted DVAW less than men. Regarding educational level and contrary to current results, educational level was significantly negatively associated with acceptability and justification of DVAW (Gracia et al, 2020; Gracia & Tomás, 2014; Tran et al, 2016).…”
Section: Discussionmentioning
confidence: 78%
“…Domestic violence against women is gender-based violence originating from discrimination against women and the normalization of violence by cultural norms. Early exercise and conditioning of DVAW begin with beliefs accepting and normalizing acts of violence (Obeid et al, 2010; Yang et al, 2021). Acceptance of violence is one of the significant factors underlying violence against women (Gracia et al, 2020; Yount et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely acknowledged that social support leads to positive mental health outcomes, improved quality of life and more willingness to seek formal support and physical safety [17,31]. Having open dialogues about the detrimental health consequences of abuse in society, coupled with more awareness about appropriate referral pathways and linkage with local support services, including helplines might motivate survivors to pursue support.…”
Section: Prevention Strategies Using the Socio-ecological Modelmentioning
confidence: 99%
“…The study also explored the impact of victim gender on young people’s attitudes towards coercive control behaviours within intimate relationships, and aimed to identify predictors of coercive awareness amongst young people. Covariates were chosen based on their potential contribution towards IPV attitudes and risk of IPV as highlighted by Yang et al ( 2021 ) as well as insights from Strand et al ( 2019 ).…”
Section: Introductionmentioning
confidence: 99%